Mechanism of reverse-offset printing. (8th June 2015) - Choi, Young-Man; Lee, Eonseok; Lee, Taik-Min
Abstract: We propose a mechanism for reverse-offset printing based on a mathematical model. In reverse-offset printing, high resolution is achieved by patterning a coated, thin ink film with an intaglio-patterned cliché. By using the relationships among the ink blanket adhesion strength, the ink cliché adhesion strength, and the ink cohesion strength, a criterion for successful patterning is derived. We found that there is a printing window in the ink blanket adhesion strength that depends on the shear strength of the ink film and the dimensions of the pattern. The printing window diminishes as the line width decreases, resulting in a minimum printable line width. The proposed mechanism was verified by printing patterns with various shapes and dimensions.